Teaching within the crisis - Καραποστόλης Βασίλης (The Greek Review of Social Research, 2011)
The basic hypothesis of this work is that one of the main victims of the recent economic crisis is the very process of learning and of knowledge. A characteristic of the present crisis is radical uncertainty, and that creates an acute contradiction. On the one hand, the markets demand that education becomes more «functional», more function-oriented. On the other hand, the same markets annul all conceptions of being functional. As a result, basic mental activities are put into question, activities such as finding a relationship between cause and effect, or moving from the part to the whole. Above all, what is disputed is the role of the teacher as a real transmitter of knowledge. Pushing the teacher aside has dire consequences which are examined in the last part of the work.